Freshmen’s Perceptions of the Effect of Technology on Learning English: A Case Study at the National University of Battambang, Cambodia - Keo Vireak; Sam Rany; Lan Bunrosy; Rouet Wen (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates first-year students' perceptions and the impact of technology integration on English language learning at the National University of Battambang (NUBB). Methodology: The research garthered data from 205 students across various majors through purposive sampling and a structured questionnaire. Data analysis involved descriptive statistics, independent sample t tests, one-way ANOVA, and regression analysis. Main Findings: The findings indicate that online searches and computer software are the most frequently utilized tools, with mobile apps and software perceived as highly effective for enhancing language skills. Students exhibit positive attitudes toward technology, contributing to improve learning outcomes. While no significant gender differences were observed in most areas, female students demonstrated lower levels of technology integration compared to males. Additionally, age did not significantly influence general technology use but affected perceptions of its effectiveness in supporting language learning. Notably, technology-assisted language learning (TALL) had the strongest positive impact on English learning outcomes. Novelty/Originality of this study: This study is original as no prior research at the National University of Battambang (NUBB) has focused on first-year students' perceptions or the impact of technology integration on English language learning. By surveying 205 freshmen from various majors using a quantitative approach, it provides a unique baseline for understanding how technology supports language acquisition in this context, addressing a critical research gap at the institution.